Editorial - Lakhal Sawsen; Martha Cleveland-Innes (The Canadian Network for Innovation in Education (CNIE), 2022)
We are pleased to publish the final 2021 issue of CJLT/RCAT which includes five empirical articles and a book review. Articles focus on teacher professional development and the use of technology in teaching and learning in elementary, secondary, and higher education. Collectively, CJLT Volume 47 Issue 3, 2021 brings together research findings from Africa (Tunisia, Kenya, and Nigeria), Asia (India), and Canada in primary, secondary, and higher education. CJLT has supported the advancement of research on teaching and learning with digital technologies in Canada and around the world and will continue to do so in the coming years. We hope that you will find in our journal some answers to the many questions that have arisen from the pedagogical transformations that have been necessary over the past two years to adapt to the pandemic context, and which open the door to pedagogical innovations in the future. We sincerely thank our reviewers for their time in reviewing the manuscripts.